2010
DOI: 10.2193/2008-579
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Landscape Occupancy by Fishers in North‐Central British Columbia

Abstract: To better understand distribution and density of fishers (Martes pennanti) in industrial forests of north‐central British Columbia, Canada, we examined factors affecting the probability of a potential home range being occupied by 10 radiotagged resident fishers in the Sub‐Boreal Spruce biogeoclimatic zone between 1996 and 2000. Percentage of a home range in wetlands and recently logged (within past 12 yr) best predicted likelihood of occupancy by each fisher. Probability of a home range area being occupied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…They offer relatively little ground structural complexity for prey and provide Fishers with little protection against weather and predators (G. P., unpublished). This finding is in agreement with previous studies in various ecozones (Proulx 2006;lancaster et al 2008;Weir and Corbould 2010).…”
Section: Introductionsupporting
confidence: 94%
“…They offer relatively little ground structural complexity for prey and provide Fishers with little protection against weather and predators (G. P., unpublished). This finding is in agreement with previous studies in various ecozones (Proulx 2006;lancaster et al 2008;Weir and Corbould 2010).…”
Section: Introductionsupporting
confidence: 94%
“…Earlier research has suggested that partial cuts maintain some of the habitat requirements of wildlife species of high Aboriginal importance, like marten (Martes americana) or fisher (Pekania pennanti), which avoid recent clearcuts (Weir andCorbould 2010, Cheveau et al 2013). Moreover, partial cuts could allow for the restoration or maintenance on the landscape of tree species of high value for Algonquin people, like eastern white-cedar (Thuja occidentalis) (Larouche et al 2007) or white pine (Pinus strobus) (Burgess et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Structure and cover have been considered critical elements for fisher habitat (Raley et al, 2012;Weir and Corbould, 2010;Truex and Zielinski, 2013). In our initial models to characterize structure, the most supported model was the landscape model with a high proportion of stands with high canopy cover.…”
Section: Habitat Selectionmentioning
confidence: 99%